PENGARUH ADOPSI IFRS TERHADAP MANAJEMEN LABA DI INDONESIA - Kurniawati, Nidya Oktavia; Ratnaningrum, Ratnaningrum (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2022)
This study aims to examine the effect of IFRS adoption on earnings management. Since 2012 Indonesia has adopted IFRS which is an internationally accepted high quality financial reporting standard. One of the characteristics of the quality of financial statements is the low level of earnings management. The population in this study are manufacturing companies listed on the Stock Exchange, with a sample of 115 companies before the adoption of IFRS and 115 companies after the adoption of IFRS. The results showed that there was no effect of IFRS adoption on earnings management practices.